2017
DOI: 10.1039/c7ce00313g
|View full text |Cite
|
Sign up to set email alerts
|

How 2-periodic coordination networks are interweaved: entanglement isomerism and polymorphism

Abstract: The entanglements of 1319 2-periodic coordination polymers are examined and fully classified using the extended ring nets (ERNs) approach. The ERNs characterize the entanglement to the greatest detail ever achieved: all possible classes/types/modes of entanglements observed and reported in the literature so far result in 216 ERN topologically distinct modes of entanglements with 74% of all the structures falling into only 21 of them. We also introduce the notion of entanglement isomerism to designate the coord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 61 publications
1
73
0
Order By: Relevance
“…3d). 13 For the mean planes of these three layers are parallel and coincident, we can see that along the a axis there still exist 1D open channels, which are occupied by the uncoordinated DMF molecules (Fig. 3e).…”
Section: Structure Description Ofmentioning
confidence: 90%
“…3d). 13 For the mean planes of these three layers are parallel and coincident, we can see that along the a axis there still exist 1D open channels, which are occupied by the uncoordinated DMF molecules (Fig. 3e).…”
Section: Structure Description Ofmentioning
confidence: 90%
“…The weaving in Figure (f) is more commonly reported in MOFs . However both weavings have been observed in MOFs . As an aside, we comment on a recent preprint, in which the author suggests that the simplest weavings of a pair of (6,3) nets is a more twisted version than those deduced here.…”
Section: Discussionmentioning
confidence: 57%
“…Escher's weaving emerges as the lowest transitivity pattern. The weaving in Figure (f) is more commonly reported in MOFs . However both weavings have been observed in MOFs .…”
Section: Discussionmentioning
confidence: 82%
“…(ii) A more sophisticated operation which has been used for the classification of coordination polymers replaces each minimal ring of edges by a node (barycentrically placed) and adds an edge between a pair of such nodes if their minimal rings are entangled. In this way one arrives at the Hopf ring net (HRN) of an embedded net N (Alexandrov et al, 2012(Alexandrov et al, , 2017. This is usually well defined as a (possibly improper) linear 3-periodic net and it has proven to be an effective discriminator in the taxonomic analysis of crystals and coordination polymer databases.…”
Section: Derived Periodic Netsmentioning
confidence: 99%
“…We note here some natural entanglement invariants of Borromean type. In fact the embedded nets of dimension type {3; 2} have been rather thoroughly identified by Carlucci et al (2014), Alexandrov et al (2017) where it is shown that subdimensional 2-periodic components can be catenated or woven in diverse ways.…”
Section: Catenation and Borromean Entanglementmentioning
confidence: 99%